The Contributions of Crosslinguistic Influence and Individual Differences to Nonnative Speech Perception - Charles B. Chang; Sungmi Kwon (Languages, 2020)
Perception of a nonnative language (L2) is known to be affected by crosslinguistic transfer from a listener’s native language (L1), but the relative importance of L1 transfer vis-a-vis individual learner differences remains unclear. This study explored the hypothesis that the nature of L1 transfer changes as learners gain experience with the L2, such that individual differences are more influential at earlier stages of learning and L1 transfer is more influential at later stages of learning. To test this hypothesis, novice L2 learners of Korean from diverse L1 backgrounds were examined in a pretest-posttest design with respect to their perceptual acquisition of novel L2 consonant contrasts (the three-way Korean laryngeal contrast among lenis, fortis, and aspirated plosives) and vowel contrasts (/o/-/ʌ/, /u/-/ɨ/). Whereas pretest performance showed little evidence of L1 effects, posttest performance showed significant L1 transfer. Furthermore, pretest performance did not predict posttest performance. These findings support the view that L1 knowledge influences L2 perception dynamically, according to the amount of L2 knowledge available to learners at that time. That is, both individual differences and L1 knowledge play a role in L2 perception, but to different degrees over the course of L2 development.